Relation entre l'intérêt d'apprentissage et les résultats d’étude de français les élèves de lycée à Semarang - Eka Santi Widyastono; Mohamad Syaefudin (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2024)
This research focuses on the relationship between students' interest in learning and students' success in French language subjects. The objectives of this research are 1. to determine the correlation between students' interest in learning and students' success in French language subjects; 2. to discover the factors that influence students' interest in learning. The number of samples in this research was 36 students of Class XII Science 3 SMA Negeri 11 Semarang. This research uses a quantitative research design. Data was collected using questionnaires to obtain information on students' learning interests and documentation to obtain information on students' learning outcomes. The data analysis used the product moment formula, the calculated r was 0.346 and for the table r, it was 0.367. Based on this analysis, it can be concluded that the calculated r is smaller than the table r, so Ho is accepted, which means that there is no relationship between students' interest in learning and the success of students in French at SMA Negeri 11 Semarang.